Optimized biodiesel production by using ultrasound assisted transesterification / Omar Saifuddin Aasimudin - Omar Saifuddin , Aasimudin (2021)
In order to combat the world crisis of consuming fossil fuel energy, biodiesel has been an alternative to fossil fuel as the clean burning fuel. Despite the effort to make a more environmentally friendly biofuel, there are challenges that comes with it. The current commercial biodiesel in Malaysia utilizes only palm oil as the feedstock in which the feedstock is used in food industry as well, so there is a stiff competition in obtaining it. Waste cooking oil and jatropha oil are added to the palm oil feedstock to lessen the use of palm oil. Since jatropha oil is a promising aspect in Malaysia and also a nonedible oil there will not be a competition from the food industry. Moreover, to fully utilize the waste cooking oil from being disposed and gone to waste, the three feedstocks are being mixed together as a feedstock. The feedstock will be converted into biodiesel through an ultrasonic assisted transesterification. Due to its efficiency, time and energy saving method compared to the conventional method. The physicochemical properties of viscosity, density, acid value, higher heating value, flash point, oxidation stability, and fatty acid methyl ester content of the biodiesel were being studied and compared to commercial biodiesel and biodiesel standard EN14214. The results proved that compared to the palm oil biodiesl, the density at 15°C of WC50J15P35 biodiesel has improved by 0.9%, the acid value improved by 13.6%, the higher heating value improved by 0.3%, the oxidation stability improved by 24%, and lastly, the flash point has improved by 1.6%. Meanwhile the obtained kinematic viscosity at 40°C is 4.504 mm2/s, The FFA content is 0.22, and the percentage yield is 91%.